Myocardial Depression and Inhibition of Positive Inotropic Effect of Digoxin by Rosiglitazone - Said, Shehta A.; Nader, Manar A. (Journal of Food and Pharmaceutical Sciences, 2013)
This study was taken to investigate the effect of rosiglitazone (RGN) on the contractility of the isolated rat atrium as well as its possible inhibitory effect on positive inotropic effect of digoxin. RGN significantly increased the dose of digoxin required to produce cardiac arrest in anesthetized rats. RGN (10, 20, 40, 60, 80 & 100 µM) produced concentration dependant depressant effect on atrial contractility  in both diabetic and non-diabetic animals with  the depressant  effect was more  pronounced  in  diabetic  rats  than  in  non-diabetic  ones.  RGN also  inhibited  the positive  inotropic effect of digoxin  (0.1, 0.3 &  1µM)  in  isolated  rat  right atrium  treated  with  4  mg/kg  orally  daily  for  21  days.  Moreover,  RGN  also  produced significant increase in serum K+ and decrease in Na+ levels in rats. These results indicate that RGN has a negative  inotropic effect on  the heart especially  in diabetics and  it  inhibits  the positive inotropic effect of digoxin.